Community-Based Sharia Economic Empowerment in Legok Village, Lohbener District, Indramayu Regency - Ulifah Sarih; Didik Himmawan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study examines the potential and implementation of community-based sharia economic empowerment in Legok Village, Indramayu, an area with significant but underdeveloped agricultural and UMKM potential. Despite its diverse economic potential, entrepreneurs in Legok Village still face serious obstacles in terms of access to capital, marketing, and business management, largely relying on high-interest conventional loans and minimal digital literacy. This study aims to analyze how the implementation of sharia economics can be a transformative solution. Using a qualitative approach with a descriptive case study method, this study collected data through interviews, observations, and documentation from UMKM, sharia cooperative administrators, village officials, and the general public. The results show that the introduction and application of sharia economic principles, such as mudharabah (profit-sharing) and qardhul hasan (interest-free loans), as well as the utilization of ZISWAF (Zakat, Infaq, Sedekah, and Waqf), have helped overcome capital constraints. Furthermore, education on sharia principles in business, such as honesty, transparency, and togetherness, has begun to shape a more ethical local business culture. Economic development efforts also include the establishment of sharia savings and loan groups, the integration of sharia values into Village-Owned Enterprises (BUMDes), and the development of sharia community markets. With the support of the village government and collaboration with sharia financial institutions, this empowerment not only increases business capacity and market access but also strengthens community solidarity and social resilience through the values of honesty and trustworthiness. This study concludes that sharia economic empowerment in Legok Village has significant potential to become a model for equitable, independent, and sustainable community economic development, aligned with local and religious values.